Pharmacological Properties of Banana Stem: An Updated Review - Kendole, Samrudhi S.; Priya, K.M. Lakshmi; Murugan, Rajadurai; Eshanya, T.V. (Journal of Nutritional Therapeutics, 2022)
Musaceae is a perennial tree-like plant that is cultivated all over the world in various tropical and subtropical regions. The fruit, peel, leaves, pseudo-stem, stalk, and inflorescence (flower) of this plant, among other parts, are utilized in traditional medicine to treat several health problems. The banana stem juice has potential biological effects, including anti-diabetic, anti-inflammatory, anti-microbial, anti-helminthic, wound-healing, anti-cancer, anti-oxidant, and anti-urolithic activities. Consequently, it can be said that banana stem juice contains adequate levels of healthy secondary metabolites that are essential for maintaining good health. To find novel approaches for treating and preventing a wide range of medical diseases, more studies into the medicinal potential of banana stem juice can be done. Hence, this review emphasizes Musaceae stem juice’s medicinal and nutritional benefits as review.